Estabelecimento do cariótipo molecular e associações sintênicas entre tripanossomas de morcegos do clado Trypanosoma cruzi - Cavalcante, Caroline Cortez [UNIFESP] (2017)
The genus Trypanosoma comprises hemoflagellate parasites generally transmitted to vertebrate host by hematophagous arthropods. The clade Schizotrypanum (Trypanosoma cruzi and T. cruzi-like) includes pathogenic and non-pathogenic trypanosomes of mammals (terrestrial and bats) of South America: T. cruzi, Trypanosoma cruzi marinkellei, Trypanosoma dionisii, Trypanosoma conorhini, and other related isolates (T. cruzi bat, T. rangeli-like). T. cruzi taxon includes trypanosomes isolated from Brazilian bats identified as T. cruzi bat and T. cruzi marinkellei, prevalent in bats from Central and South America. Bat trypanosomes are very interesting at the evolutionary level, since it has been proposed that T. cruzi and T. rangeli evolved from lineages of bat trypanosome that have switched into terrestrial mammals (“bat” seeding hypothesys). Analyses of chromosomal organization and syntenic associations of bat trypanosomes of clade T. cruzi is an important step in the study of T. cruzi chromosome evolution. Here we compared the T. cruzi karyotype with those of three bat trypanosome isolates from the clade T. cruzi (T. cruzi marinkellei, T. dionisii and T. cruzi bat) by hybridization of the chromosomal bands separated by pulsed field electrophoresis (PFGE) with chromosome-specific markers and comparative genomic hybridization based on DNA microarray (aCGH). The karyotypes of T. cruzi bat, T. cruzi marinkellei and T. dionisii were defined using clone CL Brener (TcVI strain) and T. cruzi strain G (TcI strain) as reference. Taking into consideration the number and size of chromosomal bands, the karyotypes of T. cruzi marinkellei and T. cruzi bat are very close to that of T. cruzi (lineage TcI). T. dionisii have significant differences in relation to isolates of clade T. cruzi, in agreement to previous studies that suggest T. dionisii is phylogenetically distant from T. cruzi. Hybridization of chromosomal bands with chromosome-specific markers has shown that several syntenic blocks defined in T. cruzi are also conserved in isolates of clade T. cruzi. Some alterations could be explained by segmental duplication followed by translocation to another chromosome or deletion and / or duplication of chromosomal ends by ectopic recombination. The genomes of T. cruzi bat, T. cruzi marinkellei and T. dionisii were compared to that of clone CL Brener by aCGH. It was identified 81 chromosomal alterations (47 gains, 34 losses) being 24 in T. cruzi bat, 16 in T. cruzi marinkellei and 41 in T. dionisii. Differences between T. cruzi marinkellei and T. cruzi are consistent with the low number of repeated sequences, including multigenic families, in T cruzi marinkellei. Several of syntenic relationships established by hybridization of chromosomal bands with chromosome-specific markers were validated by aCGH. Gain or loss regions can be correlated with events of segmental duplication and translocation. We have also detected gain or loss events resulting from deletion and / or duplication of the chromosomal ends by ectopic recombination. T. cruzi marinkellei appears to have completely duplicated the chromosome TcCh39 changing the number of copies of this chromosome (aneuploidy). Taken together, our results suggest that the bat isolates of clade T. cruzi seem capable of generating genetic variability in the absence of sexual reproduction, but without compromising the gene core responsible for their vital activities.